2021
DOI: 10.1073/pnas.2013284118
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic climate change is worsening North American pollen seasons

Abstract: Airborne pollen has major respiratory health impacts and anthropogenic climate change may increase pollen concentrations and extend pollen seasons. While greenhouse and field studies indicate that pollen concentrations are correlated with temperature, a formal detection and attribution of the role of anthropogenic climate change in continental pollen seasons is urgently needed. Here, we use long-term pollen data from 60 North American stations from 1990 to 2018, spanning 821 site-years of data, and Earth syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(112 citation statements)
references
References 42 publications
5
98
1
8
Order By: Relevance
“…Increasing temperature during the pre-season period is the main driver for advancement of spring and early summer flowering plants, with plant-specific reactions to the changes ( Menzel et al, 2020 ; Parmesan, 2007 ; Rojo et al, 2021 ). A recent North American study, evaluating continental pollen trends between 1990 and 2018, found that temperature was the strongest predictor of pollen season onset and explained 14–37% of the multi-decade variance ( Anderegg et al, 2021 ). There are still many open questions in phenology modelling of the start of flowering, especially the influence of chilling and photoperiod and to how plants will react to increasing temperatures in the future ( Basler, 2016 ; Fu et al, 2015 ; Güsewell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing temperature during the pre-season period is the main driver for advancement of spring and early summer flowering plants, with plant-specific reactions to the changes ( Menzel et al, 2020 ; Parmesan, 2007 ; Rojo et al, 2021 ). A recent North American study, evaluating continental pollen trends between 1990 and 2018, found that temperature was the strongest predictor of pollen season onset and explained 14–37% of the multi-decade variance ( Anderegg et al, 2021 ). There are still many open questions in phenology modelling of the start of flowering, especially the influence of chilling and photoperiod and to how plants will react to increasing temperatures in the future ( Basler, 2016 ; Fu et al, 2015 ; Güsewell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1959, Switzerland has experienced an average annual warming of 0.35 °C/decade ( Ceppi et al, 2012 ). Given that climactic factors such as temperature are positively associated with plant growth, readiness for flowering, and pollen abundance ( Anderegg et al, 2021 ; Beggs, 2016 ; Clot et al, 2012 ; Dahl et al, 2013 ; Rojo et al, 2021 ), this longitudinal change is likely to have transformed the onset, duration, and intensity of pollen release. Pollen is an emerging public health risk; understanding more precisely how seasonal temporality and intensity are evolving has far-reaching implications for health system management, environmental planning, and public awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has greatly impacted the onset, duration and intensity of the pollen season in recent decades, leading to an increase in exposure to some allergenic pollen species such as birch, hazel, oak, beech, and nettle and hemp families in Switzerland (1,2). Similar shifts have been observed in other countries (3,4). At the same time, allergies to airborne pollen are increasingly common in Europe (5,6), and prevalence in Switzerland has risen from around 0.82% in 1926 to between 14 and 20%, as estimated by more recent studies (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 70%
“…Across Spain, Jato et al (20) analysing data from four Spanish sites spanning 1993-2009, found a decrease in pollen season length and severity and related this to temperature increases. Recently, Anderegg et al (21) showed, for aggregation of 60 North American pollen monitoring sites, that pollen seasons were commencing significantly earlier, lasting longer and increasing in magnitude, but when pollen was considered in separate categories; weed, grass or trees, grass pollen showed no significant trend in the annual pollen integral. Whilst there is broad agreement amongst most studies that with climate change pollen levels in general are increasing, it is difficult to definitively link airborne pollen changes with temperature and rainfall changes, and to decouple land use changes from climate change (17,(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%